Cost-utility analysis of a multispecialty interprofessional team dementia care model in Ontario, Canada - Andrew P Costa; Linda Lee; Samir K Sinha; Tejal Patel; Loretta M Hillier; William W L Wong; Sasha Walker; Catherine Lee (BMJ Open)
Objectives To examine the cost-effectiveness of Multi-specialty INterprofessional Team (MINT) Memory Clinic care in comparison to the provision of usual care.Design Using a Markov-based state transition model, we performed a cost-utility (costs and quality-adjusted life years, QALY) analysis of MINT Memory Clinic care and usual care not involving MINT Memory Clinics.Setting A primary care-based Memory Clinic in Ontario, Canada.Participants The analysis included data from a sample of 229 patients assessed in the MINT Memory Clinic between January 2019 and January 2021.Primary outcome measures Effectiveness as measured in QALY, costs (in Canadian dollars) and the incremental cost-effectiveness ratio calculated as the incremental cost per QALY gained between MINT Memory Clinics versus usual care.Results MINT Memory Clinics were found to be less expensive ($C51 496 (95% Crl $C4806 to $C119 367) while slightly improving quality of life (+0.43 (95 Crl 0.01 to 1.24) QALY) compared with usual care. The probabilistic analysis showed that MINT Memory Clinics were the superior treatment compared with usual care 98% of the time. Variation in age was found to have the greatest impact on cost-effectiveness as patients may benefit from the MINT Memory Clinics more if they receive care beginning at a younger age.Conclusion Multispecialty interprofessional memory clinic care is less costly and more effective compared with usual care and early access to care significantly reduces care costs over time. The results of this economic evaluation can inform decision-making and improvements to health system design, resource allocation and care experience for persons living with dementia. Specifically, widespread scaling of MINT Memory Clinics into existing primary care systems may assist with improving quality and access to memory care services while decreasing the growing economic and social burden of dementia.